Stress, self-regulation, and physical activity towards quality of life among senior year health science undergraduates / Arimi Fitri Mat Ludin ... [et al.] - Mat Ludin, Arimi Fitri; Mohamed Tahir, Ahmad Rashidi; Ahmad, Faisal Malau; Zin, Najwa Suhaili; Ahmad, Nurnadiah; Ismail, Nur Mashitoh; Mustafa, Nurul Hidayah; Ahmad Najdi, Samihah Aslamiah; Ibrahim, Farah Wahida; Abd Warif, Nor Malia; Ishak, Ismarulyusda (Universiti Teknologi MARA, Perlis, 2025)
Final-year university students experience considerable stress due to academic demands, high expectations, and challenges such as online learning, emotional self-regulation, and physical inactivity. Prolonged stress significantly impacts students' behaviors, influencing their quality of life (QoL), which encompasses physical, mental, and social well-being. Emotion regulation and physical activity are crucial factors for mitigating stress and enhancing overall well-being. This study aimed to explore the relationships between perceived stress, physical activity, emotional self-regulation, and their combined influence on QoL among senior-year Health Sciences students at Universiti Kebangsaan Malaysia (UKM). A cross-sectional study was conducted involving 135 senior-year students from ten Health Sciences programs, selected through stratified random sampling. Data collection employed validated self-administered questionnaires, including the Perceived Stress Scale (PSS), Self-Regulation Questionnaire (SRQ), Global Physical Activity Questionnaire (GPAQ), and WHO QOL-BREF. Descriptive statistics, correlation analysis, and multiple linear regression were conducted using SPSS to examine the relationships and predictive effects of the variables on QoL. Descriptive analysis revealed notable trends in stress, physical activity, and QoL levels. Correlation analysis indicated significant associations between perceived stress, self-regulation, and physical activity, with each factor contributing to students' overall QoL. Multiple regression analysis highlighted self-regulation and physical activity as critical predictors of QoL, while stress negatively impacted well-being. This study underscores the pivotal role of emotional self-regulation and physical activity in enhancing QoL